PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS LECTORA INSPIRE PADA MATERI JURNAL PENYESUAIAN SIKLUS AKUNTANSI PERUSAHAAN JASA UNTUK SISWA KELAS X SMK NEGERI 4 PEKANBARU (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstrack: This study aims to: (1) determine the process of developing interactive learning media based on Lectora Inspire; (2) determine the feasibility of developing interactive learning media based on validation from material experts and media experts; (3) knowing students' assesment of interactive learning media based on Lectora Inspire. This type of research and development uses the ADDIE development model. This study uses qualitative and quantitative data with data collection instruments in the form of a questionnaire. This interactive learning media was validated by one material expert and one media expert, and was tested on 20 students of class X Accounting and Finance of SMK Negeri 4 Pekanbaru. The results showed that: (1) Lectora Inspire-Based Learning Media was developed through five stages, namely (a) Analysis, b) Design, c) Development d) Implementation and e) Evaluation ( evaluation); (2) the feasibility of interactive learning media based on Lectora Inspire based on the assessment of material experts as many as 78% which are included in the "adequate" category and 93% of media experts who are included in the "very feasible" category; (3) The assessment of students of class X Accounting and Finance of SMK Negeri 4 Pekanbaru obtained a total of 89% which is included in the "very decent" category. Based on the results of this study, the interactive learning media based on Lectora Inspire that was developed is very suitable to be used as a medium for learning accounting.Keywords: Interactive Learning Media, Lectora Inspire, Adjustment Journal.